2020
DOI: 10.1155/2020/6659314
|View full text |Cite|
|
Sign up to set email alerts
|

Water Quality Prediction Using Artificial Intelligence Algorithms

Abstract: During the last years, water quality has been threatened by various pollutants. Therefore, modeling and predicting water quality have become very important in controlling water pollution. In this work, advanced artificial intelligence (AI) algorithms are developed to predict water quality index (WQI) and water quality classification (WQC). For the WQI prediction, artificial neural network models, namely nonlinear autoregressive neural network (NARNET) and long short-term memory (LSTM) deep learning algorithm, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(91 citation statements)
references
References 38 publications
1
89
1
Order By: Relevance
“…Deep learning algorithms use many deeper hidden layers to surpass classical ANN methods. [46,47]. A convolutional neural network is one of the most popular deep neural network algorithms, and it is named convolution by using mathematical linear operation between matrices.…”
Section: Correlation Analysismentioning
confidence: 99%
“…Deep learning algorithms use many deeper hidden layers to surpass classical ANN methods. [46,47]. A convolutional neural network is one of the most popular deep neural network algorithms, and it is named convolution by using mathematical linear operation between matrices.…”
Section: Correlation Analysismentioning
confidence: 99%
“…It has the power to be adjusted in order to lower its error without being sure that the error could not be lower still [10]. e authors in [11] considered ANN among the most powerful machine learning algorithms for time-series predictions. A large-scale empirical comparison between ten supervised learning methods demonstrated that neural networks are more competitive and efficient than boosting, random forests, bagging, and support vector machines [12].…”
Section: Artificial Neural Network (Ann)mentioning
confidence: 99%
“…However, this model only considers single‐dimensional input, while there are more complex datasets with many different dimensions for water quality monitoring. Aldhyani et al (2020) proposed a model by using advanced artificial intelligence algorithms to measure the future water quality. The SVM algorithm has achieved the highest accuracy; however, the analysis should be extended to different types of water.…”
Section: Motivationmentioning
confidence: 99%